2020
DOI: 10.3390/nu12102994
|View full text |Cite
|
Sign up to set email alerts
|

Barriers towards Sun Exposure and Strategies to Overcome These Barriers in Female Indoor Workers with Insufficient Vitamin D: A Qualitative Approach

Abstract: The prevalence of vitamin D insufficiency is significant even in tropical countries such as Malaysia. Sun exposure is the primary source of vitamin D for most people due to limited intakes of food containing vitamin D and supplements. This study explored the perception of barriers towards sun exposure and strategies to overcome these barriers among vitamin D insufficient women workers in Kuala Lumpur, Malaysia. Twenty-five female indoor workers with serum 25-hydroxyvitamin D < 50 nmol/L participated in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…However, there are numerous reasons why Malaysians tend to avoid sun exposure. Some of the barriers to sun exposure identified amongst Malay women with low vitamin D status include misunderstanding about vitamin D, health concerns toward sun exposure, including effects on skin color and surface, weather (hot and rainy), and religious/cultural clothing practices (76). Additionally, there are limited studies investigating vitamin D synthesis following sun exposure in Malaysia (77).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are numerous reasons why Malaysians tend to avoid sun exposure. Some of the barriers to sun exposure identified amongst Malay women with low vitamin D status include misunderstanding about vitamin D, health concerns toward sun exposure, including effects on skin color and surface, weather (hot and rainy), and religious/cultural clothing practices (76). Additionally, there are limited studies investigating vitamin D synthesis following sun exposure in Malaysia (77).…”
Section: Discussionmentioning
confidence: 99%
“…Pada mahasiswa perempuan, ditambah dengan kekhawatiran kulitnya akan menjadi gelap atau berbintik hitam jika terpapar sinar matahari. Sejalan dengan studi pada perempuan pekerja di Malaysia yang melaporkan bahwa perempuan takut memiliki kulit gelap, bintik-bintik, kulit terbakar matahari sehingga mempengaruhi perilakunya untuk menghindari sinar matahari (27). Hal ini juga kemungkinan menyebabkan kadar vitamin D dalam darah perempuan lebih rendah jika dibandingkan laki-laki.…”
Section: Bahasanunclassified
“…Study in Sri Lanka revealed limited sunlight exposure among university health care students ( 30 ). In addition, the influence of modern urban lifestyles, prevalent in this population, has been identified as one of the causes of reduced sunlight exposure ( 31 ). Factors such as poor knowledge about the importance of vitamin D, spending long hours in academic facilities such as laboratories, and predominantly sedentary study habits contribute to this low sunlight exposure in students ( 30 , 32 ).…”
Section: Introductionmentioning
confidence: 99%